10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Neurological deterioration, headache, vomiting, bradycardia, or hypertension after emergent percutaneous coronary intervention should prompt immediate brain imaging. When subarachnoid hemorrhage is detected shortly after coronary stenting, the hemorrhage onset may remain uncertain, and antiplatelet decisions require individualized multidisciplinary assessment.